Rice Field Carrying Capacity as A Source of Ruminant Feed in the Rice-Cattle Integration System - Husnaeni, Husnaeni; Suparman, Suparman; Bahari, Doddy Ismunandar; Tatra, Afsitin Joan (Jurnal Agripet, 2025)
Kolaka Regency is recognised not only as a major rice producer but also as an important centre for smallholder livestock farming. The Rice-Cattle Integration System (R-CIS) has been identified as an effective approach to optimize local agricultural resources for smallholder livestock development. However, its dissemination has remained limited due to the uneven carrying capacity of rice fields across different regions. This study aimed to analyse the current and projected carrying capacity of rice fields in Kolaka Regency, Southeast Sulawesi (20232024), considering land availability, livestock population, and feed resources. Data analysis included assessments of land carrying capacity, livestock density, livestock concentration index (LCI), and feed concentration index (FCI). Results indicated that Kolaka had 12,203 ha of rice fields, producing 3,188 tons of crude protein (CP) annually from unfermented rice straw and 10,539 tons CP/year from fermented straw. Feed distribution within the regency was uneven: in districts such as Baula, Pomalaa, Samaturu, Wolo, and Wundulako, livestock populations could be increased, whereas Toari and Watubangga exceeded carrying capacity even after straw fermentation. The study estimated that fermented straw could support an additional 24,335 livestock units (LU) across Kolaka Regency, equivalent to about 2,028 LU per district annually. These findings highlight the need for inter-district feed substitution and livestock redistribution. Overall, fermented rice straw significantly enhanced feed availability, thereby supporting sustainable livestock production.